IN.PACT SFA Clinical Study Using the IN.PACT Admiral Drug-Coated Balloon in a Chinese Patient Population. (August 2019) - Chen, Zhong; Guo, Wei; Jiang, Weiliang; Wang, Feng; Fu, Weiguo; Zou, Yinghua; Deckers, Stefanie; Li, Pei; Popma, Jeffrey J.; Jaff, Michael R.
Purpose: To confirm the safety and effectiveness of the IN.PACT Admiral drug-coated balloon (DCB) as a treatment for de novo and native artery restenotic lesions in the superficial femoral artery (SFA) and/or proximal popliteal artery in Chinese subjects.Materials and Methods: IN.PACT SFA China ( ClinicalTrials.gov identifier NCT02118532) was a single-arm, independently adjudicated, prospective, premarket study that enrolled 143 subjects (mean age 66.8±7.7 years; 107 men) at 15 centers. The predominant risk factors were hypertension (104, 72.7%) and diabetes mellitus (66, 46.2%). The majority of subjects were classified as Rutherford category 2 or 3 [69 (48.3%) and 55 (38.5%), respectively]; 19 (13.3%) subjects had critical limb ischemia (Rutherford category 4). The mean lesion length was 10.4±6.51 cm; more than half of the lesions (75, 52.4%) were chronic total occlusions. Calcification was found in 66 (46.2%) lesions. Outcomes at 12 months were compared with DCB safety and effectiveness performance goals derived from the literature. The 30-day primary safety outcome was a composite of freedom from device- and procedure-related mortality, major target limb amputation, and clinically-driven target lesion revascularization (CD-TLR).Results: The primary safety outcome was 99.3% at 30 days. Follow-up compliance at 12 months was 92.6%. Estimated 1-year primary patency using Kaplan-Meier analysis was 90.9% and freedom from CD-TLR was 97.1%. The rate of CD-TLR at 12 months was 2.9%. The Rutherford category status improved significantly (p<0.001) between baseline and 12 months.Conclusion: Results from IN.PACT SFA China demonstrated high rates of patency and low rates of CD-TLR in Chinese subjects through 12 months despite patient and lesion complexity. These data are consistent with the results of other IN.PACT DCB trials.